Dysphotopsia after uneventful phacoemulsification - Mohammed A. Mohammed (Journal of the Egyptian Ophthalmological Society)
Background Unexpected negative visual outcomes, especially after uneventful phacoemulsification, are frustrating to patients and surgeons. Dysphotopsia is one of the main causes of this dissatisfaction after uneventful phacoemulsification. Our study aimed to describe the prevalence of this type of dysphotopsia after uneventful phacoemulsification in our practice at Suez hospitals department. Patients and methods This study was conducted at the Ophthalmology Outpatient Clinic of Suez General Hospital on 120 eyes from 120 patients who underwent uncomplicated phacoemulsification and intraocular lens implantation from January to April 2024. Subjectively, patients were asked about dysphotopsia symptoms 1 month after surgery, and their symptoms were improved with conservative treatment. We reviewed pathophysiology and various treatment modalities that are accessible, such as observation, nonsurgical correction options such as conservative management, medication-assisted miosis, optical correction, and surgical correction options as a last resort for serious cases. Results Six cases of dysphotopsia (5%) were identified among the 120 patients in the study: 2 patients recorded negative dysphotopsia (1.7%), and 4 patients had positive dysphotopsia (3.3%). Conclusion Patients now anticipate satisfaction from cataract surgery, which is becoming a common procedure. Both the patient and the surgeon may become frustrated when dysphotopsia occurs, which incidentally occurs in a flawlessly performed procedure. In our study, 6 patients out of 120 patients had dysphotopsia, which was resolved with conservative treatment only. Enhancing treatment and preventing this specific cause of postoperative complaints may be achieved by having a thorough understanding of this matter, its possible risk factors, and its successful methods of management.